2018
DOI: 10.1053/j.gastro.2018.05.041
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoke Induces Stem Cell Features of Pancreatic Cancer Cells via PAF1

Abstract: Exposure to cigarette smoke activates stem cell features of pancreatic cells, via CHRNA7 signaling and FOSL1 activation of PAF1 expression. Levels of PAF1 are increased in pancreatic tumors of humans and mice with chronic cigarette smoke exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
58
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(61 citation statements)
references
References 42 publications
2
58
1
Order By: Relevance
“…Furthermore, recent studies have indicated that FOSL1 plays an important role in the regulation of epithelial‐mesenchymal transition, which is associated with tumor metastasis . Additionally, our data (Figure and Table ) and other published data all showed that pancreatic cancer tissues have a slightly higher expression of FOSL1 compared with normal pancreatic tissues. All of these results imply that agents that can downregulate the expression of FOSL1 might have potential to be used for the treatment of PDAC.…”
Section: Introductionsupporting
confidence: 81%
“…Furthermore, recent studies have indicated that FOSL1 plays an important role in the regulation of epithelial‐mesenchymal transition, which is associated with tumor metastasis . Additionally, our data (Figure and Table ) and other published data all showed that pancreatic cancer tissues have a slightly higher expression of FOSL1 compared with normal pancreatic tissues. All of these results imply that agents that can downregulate the expression of FOSL1 might have potential to be used for the treatment of PDAC.…”
Section: Introductionsupporting
confidence: 81%
“…Subsequently, various signalling pathways are activated, such as Wnt/‐catenin, Ras/Raf/MEK/ERK, PI3K/Akt and JAK2/Stat3, leading to the promotion of tumour cell proliferation, EMT and migration . Nicotine and its derivatives such as NNK and NNN, can not only activate nAChRs, studies have also shown that lung cancers synthesize acetylcholine (ACh) and cytokines, which acted as autocrine growth factors that stimulate nAChRs in lung cancer despite a lack of exogenous nicotine . EMT is a key initiating event in the metastatic cascades of various cancers .…”
Section: Discussionmentioning
confidence: 99%
“…[36][37][38][39][40] Nicotine and its derivatives such as NNK and NNN, can not only activate nAChRs, studies have also shown that lung cancers synthesize acetylcholine (ACh) and cytokines, which acted as autocrine growth factors that stimulate nAChRs in lung cancer despite a lack of exogenous nicotine. 41,42 EMT is a key initiating event in the metastatic cascades of various cancers. [43][44][45] The molecular mechanism of α5-nAChR in lung cancer EMT is far from clear.…”
Section: Discussionmentioning
confidence: 99%
“…EZH2, BMI1) are major drivers of stem cells, and a group of researchers from the University of Queensland have proposed BMI1 and EZH2 as prostate and oral CSC markers, respectively [89,91]. We have identified the novel role of PAF1/PD2 in the maintenance of ovarian and pancreatic CSCs, demonstrating that PAF1/PD2 interacts with Oct3/4 or PHF5A and maintains the stem cell features of ovarian/pancreatic CSCs [9294]. It is also known that VEGF promotes stemness and has been shown as a breast CSC marker [95].…”
Section: Manifold Existence Of Cancer Stem Cells and Its Impact On Camentioning
confidence: 99%